Cryptosystem Polyalphabetic Cipher Application - Muhlisatul Mahmudah; Tri Novita Irawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2020)
Polyalphabetic cipher cryptosystem is the study of mathematical techniques that related to aspects of information security such as confidentiality, data integrity, authentication and authentication of data origin. With the internet, long distance communication can be done quickly and cheaply. However, the internet is not very secure because it is a public communication medium that can be used by anyone so it is very vulnerable to information tapping. Cryptography has been widely used in life for example banking atm ATMs, account numbers sacrificed, sending secret military messages. By applying polyalphabetic cipher cryptosystems, pins, account numbers and secret messages sent will be more secure and the information will not be easily known. Keywords: polyalphabetic cipher cryptosystem, banking, pin